A Modified Grey Wolf Algorithm with Applications to Engineering - Vahid Mahboub (مجله مدل سازی در مهندسی)
In this contribution, a modified gray wolf algorithm for use in engineering applications is presented. The grey wolf algorithm is one of the meta-heuristic optimization methods that has recently been widely used by researchers due to its good capabilities. The mechanism is free of derivation, simple in execution and implementation, and only needs target function as input of the problem, among other things that make the gray wolf algorithm popular and of interest. But the problem that can be mentioned about it is that the decreasing factor used in it is linear and in some non-linear problems, it may cause more error or late convergence to the original solution. This bottleneck is solved by presenting a modified grey wolf algorithm. Then the results are compared in the form of an applied numerical example in engineering sciences with the classic grey wolf algorithm and some similar proposed coefficients to determine the efficiency of the modified algorithm.